2015
DOI: 10.1016/j.sbspro.2015.07.401
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Irrational Beliefs on Academic Motivation and Academic Self-efficacy of Candidate Teachers of Computer and Instructional Technologies Education Department

Abstract: Irrational beliefs are improper solutions developed by the person himself for his personal problems. They occur in person's mind. These beliefs affect person's life. The purpose of this research is to investigate the effects of irrational beliefs on academic motivation and academic self-efficacy of students. Independent variable of the study is irrational beliefs. Dependent variables are academic motivation and academic self-efficacy. Survey method was used in the study. The sample of the study consists of 161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…This means that when levels of academic motivation increased, irrational beliefs also increased. Ozer and Akgun (2015) also confirmed that when academic motivation increased, there was a moderate increase in academic self-sufficiency.…”
Section: The Relationship Between Academic Motivation and Academic Acsupporting
confidence: 64%
See 2 more Smart Citations
“…This means that when levels of academic motivation increased, irrational beliefs also increased. Ozer and Akgun (2015) also confirmed that when academic motivation increased, there was a moderate increase in academic self-sufficiency.…”
Section: The Relationship Between Academic Motivation and Academic Acsupporting
confidence: 64%
“…While the assessment of the frequency of worry rather than the level may have been more appropriate, the study denotes that worry does affect levels of self-efficacy and achievement (Tang & Westwood, 2007). Ozer & Akgun (2015) confirmed that there is a positive relationship between irrational beliefs, academic motivation, and academic self-sufficiency. When academic motivation increases, there is a moderate increase in academic self-sufficiency.…”
Section: Summary Of Literaturementioning
confidence: 71%
See 1 more Smart Citation
“…At the same time, it has been proved that irrational beliefs are associated not only with various human dysfunctions but also with normal psyche and motivation for activity [20]. Irrational beliefs are actively studied in modern science in the framework of medicine and psychology [21], education [22], sports [23], and others. Regarding the influence of irrational beliefs on people's attitudes towards dangers, there is only evidence of the relationship between irrational attitudes and anxiety, which often leads to the desire to exaggerate dangers [24].…”
Section: Introductionmentioning
confidence: 99%
“…Selfefficacy, assurance of their ability to successfully complete assignments, interact with others, and successful management of work and family. 9,10 People with high selfefficacy, unlike people with low self-efficacy, use higherlevel intellectual processes to solve problems and imagine themselves successful in challenging assignments. 11 In other words, self-efficacy is the perception of individuals of a specific range of abilities to perform the necessary actions to achieve valuable goals.…”
Section: Introductionmentioning
confidence: 99%